Relationship between altitude and the prevalence of hypertension in Tibet: a systematic review - Mingji, Cuomu; Onakpoya, Igho J; Perera, Rafael; Ward, Alison M; Heneghan, Carl J (Heart (British Cardiac Society), 2015)
IntroductionHypertension is a leading cause of cardiovascular disease, which is the cause of one-third of global deaths and is a primary and rising contributor to the global disease burden. The objective of this systematic review was to determine the prevalence and awareness of hypertension among the inhabitants of Tibet and its association with altitude, using the data from published observational studies.MethodsWe conducted electronic searches in Medline, Embase, ISI Web of Science and Global Health. No gender or language restrictions were imposed. We assessed the methodological characteristics of included studies using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) criteria. Two reviewers independently determined the eligibility of studies, assessed the methodology of included studies and extracted the data. We used meta-regression to estimate the degree of change in hypertension prevalence with increasing altitude.ResultsWe identified 22 eligible articles of which eight cross-sectional studies with a total of 16 913 participants were included. The prevalence of hypertension ranged between 23% and 56%. A scatter plot of altitude against overall prevalence revealed a statistically significant correlation (r=0.68; p=0.04). Meta-regression analysis revealed a 2% increase in the prevalence of hypertension with every 100 m increase in altitude (p=0.06). The locations and socioeconomic status of subjects affected the awareness and subsequent treatment and control of hypertension.ConclusionsThe results from cross-sectional studies suggest that there is a significant correlation between altitude and the prevalence of hypertension among inhabitants of Tibet. The socioeconomic status of the inhabitants can influence awareness and management of hypertension. Very little research into hypertension has been conducted in other prefectures of Tibet where the altitude is much higher. Further research examining the impact of altitude on blood pressure is warranted.